STAGES OF EARLY CHILDHOOD COGNITIVE DEVELOPMENT: THE FOUNDATION OF INTELLECTUAL GROWTH - Sakinah Siregar; A. Naashir M. Tuah Lubis (Sean Institute, 2023)
Cognitive development in early childhood is an important phase in forming the foundation of a child's intellectual growth. First, the sensorimotor phase highlights the importance of sensory and motor stimulation in early childhood. Children learn through touch, sight and physical movement, which form the basis for understanding the world around them. Then, the preoperational phase marks the development of symbolic thinking and language skills. Children's creativity and imagination flourish, while their understanding of the concepts of space and time begin to develop. Next, the concrete operational phase shows the child's ability to think logically and understand abstract concepts with the help of concrete objects. Cognitive processes become more complex, and children are able to connect concepts in greater depth. Finally, the formal operational phase marks the child's ability to think abstractly and develop more complex problem-solving skills. Social interactions, educational play and supportive learning experiences all play a key role in forming the foundation of intellectual growth. This understanding also forms the basis for designing effective educational programs, ensuring that children can optimize their cognitive potential during this critical period of development.